THE INFLUENCE OF INQUIRY LEARNING MODEL WITH AUDIO VISUAL AND SCIENCE PROCESS SKILLS ON CRITICAL THINKING SKILLS IN ANIMAL AND HUMAN BREATHING MATERIALS - Kiki Wihartini; Retno Dwi Suyanti; Sriadhi Sriadhi (Sensei International Journal of Education and Linguistic, 2022)
This study aims to determine the differences in the critical thinking skills of children who are taught with the learning model inquiry with audio-visual and based on Science Process Skills, as well as the interaction between the two models with the child's Science Process Skills level in influencing the improvement of students' critical thinking skills. The research was carried out at the Nurul Hasanah Private Elementary School in the odd semester of the 2021/2022 academic year. The sample in this study consisted of classes VA and VC which were taken by purposive sampling class. The VA class as an experimental class was taught using an Audio Visual-based inquiry learning model, while the control class was taught using a direct learning model, the VC class was chosen. The type of research used in this research is quasi-experimental. The research design used is Posttest Only Control Design. Based on the results of the analysis and research findings from the field, several conclusions were obtained which were the answers to the questions in the problem formulation